STRATEGIC DOCUMENTS IN TRANSPORT AND THEIR IMPORTANCE FOR STRATEGIC ANALYSIS OF TRANSPORT COMPANIES - Oborilová, Iveta; Melichar, Vlastimil (Žilinská univerzita, 2016)
Rapidly changing economic conditions and globalization trends are emerging in the transport sector in the Czech Republic and this affects not only strategic documents at the state level, but also strategies of transport companies and their management. The Czech Republic, as a member of the European Union, has to meet its commitments ensuing from this membership, and this is reflected in national transport policy. Changes in national transport policy have an effect on the business environment in the sector and this means that the management of transport companies needs to identify these changes in time, to assess their severity and to take them into account in business activities. Economic and social aspects of transport policy are monitored from a business perspective in order to find opportunities for company strengths reinforcement, alternatively to draw attention to possible weakening. The aim of this paper is to describe important aspects of transport policy and to project their impact on the strategic analysis of the external environment processed by the transport company management.
STRATEGICKÉ DOKUMENTY V OBLASTI DOPRAVY A JEJICH VÝZNAM PRO STRATEGICKOU ANALÝZU DOPRAVNÍCH SPOLEČNOSTÍ
Keywords: transport sector; transport policy; economic and social aspects of transport policy; strategic analysis; odvětví dopravy; dopravní politika; ekonomické a sociální aspekty dopravní politiky; strategická analýza